0777 Variations in Vigilance and Sleep Among Underground Mine Workers During 14 Consecutive Night Shifts. (27th May 2020) - Laberge, L; Lavigne, A A; Auclair, J; Hébert, M
Abstract: Introduction: Adverse effects of night shift work are well known but there is scarce data on how vigilance and sleep vary across a large number of consecutive night shifts. Methods: In summer, 38 underground miners (mean age (SD): 36.8 (13.9) years) wore an actigraph, filled out the Morningness-Eveningness questionnaire, and completed a Visual Analog Scale capturing subjective vigilance (very sleepy to very alert) 4 times per shift (19:00, 22:00, 02:00, and 05:30) for 14 consecutive night shifts. Mixed effects linear regression models were used to account for repeated measures. Results: Mean vigilance level is lower at 22:00, 02:00 and 05:30 than at the beginning of the shift at 19:00 (p<0.001). Also, a more pronounced decrease in vigilance during the night was observed among older workers compared to younger workers (p<0.05). Moreover, workers with greater eveningness have higher vigilance at the beginning of the first night shift at 19:00 (p<0.001), but their decline in vigilance level during the night is faster than that observed in workers with greater morningness (p<0.01). Interestingly, the mean vigilance decline observed at 02:00 and 05:30 (compared to 19:00) is slowed down for each additional night shift (p<0.001). Furthermore, mean sleep efficiency is negatively associated with morningness and gradually decreases across consecutive night shifts (p<0.05). In addition, mean sleep duration is shorter in older workers and is positively associated with morningness (p<0.05). Conclusion: Results show a progressive improvement in vigilance of mine workers assigned to a large number of consecutive 12-hour night shifts from 2 am onwards. This may probably be ascribed to an adjustment in homeostatic sleep propensity consecutive to the partial sleep deprivation associated with time spent traveling to the remote site before the first shift. However, circadian adjustment is unlikely considering the strong morning light exposure experienced daily after the night shift. Support: College and Community Innovation Program of the Natural Sciences and Engineering Research Council of Canada (NSERC) (CUI2I 472201-14)